Relationships between experiential risk, experiential benefits, experiential evaluation, experiential co-creation, experiential relationship quality, and future experiential intentions to travel with pets. (January 2020) - Wu, Hung-Che; Cheng, Ching-Chan
Previous studies have paid great attention to exploring relevant issues of risk, benefits, evaluation, co-creation, relationship quality dimensions (satisfaction and trust), and future intentions; however, none focuses on them from experiential perspectives in the tourism industry. The purpose of this study is to explore the structural relationships between experiential risk, experiential benefits, experiential evaluation, experiential co-creation, experiential relationship quality dimensions (experiential satisfaction and experiential trust), and future experiential intentions based on pet owners' experiences of traveling with pets. A questionnaire survey was used to collect the data from respondents who traveled with their dogs to Goolawah Regional Park of New South Wales, obtaining 537 valid samples which were analyzed with structural equation modeling. The study results can show tourism operators what constitutes pet owners' experiences and can aid them in decreasing experiential risk and increasing experiential benefits, experiential evaluation, experiential co-creation, experiential satisfaction, experiential trust, and future intentions to have a travel experience with their pets.